Hybris, ancient and modern (Revista Archai, 2024)
This article explores key connections between modern and ancient hybris, drawing insights from psychology and corporate studies as well as classical scholarship. It focuses particularly on Aristotle's discussions of the topic in the Rhetoric and Politics, while also examining other classical sources, including Herodotus and Aeschylus.